18F-APN-1607 Tau Positron Emission Tomography Imaging for Evaluating Disease Progression in Alzheimer’s Disease - Xu, Xiaojun; Ruan, Weiwei; Liu, Fang; Gai, Yongkang; Liu, Qingyao; Su, Ying; Liang, Zhihou; Sun, Xun; Lan, Xiaoli (Frontiers in Aging Neuroscience, 2022)
Purpose: 18F-APN-1607 is a novel tau PET tracer characterized with high binding affinity for 3- and 4-repeat tau deposits. The aim was to analyze the spatial distribution of 18F-APN-1607 PET imaging in Alzheimer’s disease (AD) subjects with different stages, and to investigate the relationship between the change of tau deposition and overall disease progression. Methods: We retrospectively analyzed the 18F-APN-1607 PET imaging of 31 subjects with clinically and imaging defined as AD. According to the Mini-mental State Examination (MMSE) score, patients were divided into three groups, mild (≥21, n=7), moderate (10-20, n=16) and severe (≤9, n=8). PET imaging was segmented to 70 regions of interest (ROIs) and extracted the standard uptake value (SUV) of each ROI. The regions were defined as positive and negative with unsupervised cluster analysis according to SUVR. The SUVRs of each region were compared among groups with the one-way analysis of variance or Kruskal-Wallis H test. Further, the correlations between MMSE score and regional SUVR were calculated with Pearson or Spearman correlation analysis. Results: There were no significant differences among groups in gender (χ2=3.814, P=0.161), age of onset (P=0.170), age (P=0.109), and education level (P=0.065). With the disease progression, the 18F-APN-1607 PET imaging showed the spread of tau deposition from hippocampus, posterior cingulate gyrus (PCG) and lateral temporal cortex (LTC), to parietal lobe and occipital lobe, finally to frontal lobe. Between the mild and moderate group, the main brain areas with significant differences in 18F-APN-1607 uptake were supplementary motor area (SMA), cuneus, precuneus, occipital lobule, paracentral lobule, right angular gyrus, parietal, which could be used for early disease progression assessment (P<0.05). There were significant differences in frontal lobe, right temporal lobe and fusiform gyrus between the moderate and severe group, which might be suitable for late-stage disease progression assessment (P<0.05). Conclusions: 18F-APN-1607 PET may serve as an effective imaging marker for visualizing the change pattern of tau protein deposition in AD patient, and its uptake level in certain brain regions showed closely related to the severity of cognitive impairment. These indicated the potential of 18F-APN-1607 PET for in vivo evaluating the progression of AD.